Mediation Role of Physical Fitness and Its Components on the Association Between Distribution-Related Fat Indicators and Adolescents’ Cognitive Performance: Exploring the Influence of School Vulnerability. The Cogni-Action Project - Hernández-Jaña, Sam; Sanchez-Martinez, Javier; Solis-Urra, Patricio; Esteban-Cornejo, Irene; Castro-Piñero, Jose; Sadarangani, Kabir P.; Aguilar-Farias, Nicolas; Ferrari, Gerson; Cristi-Montero, Carlos (Frontiers in Behavioral Neuroscience, 2021)
Background: Physical fitness and fatness converge simultaneously modulating cognitive skills, which in turn, are associated with children and adolescents’ socioeconomic background. However, both fitness components and fat mass localization are crucial for understanding its implication at the cognitive level. Objective: This study aimed to determine the mediation role of a global physical fitness score and its components on the association between different fatness indicators related to fat distribution and adolescents’ cognitive performance, and simultaneously explore the influence of school vulnerability. Methods: In this study, 1,196 Chilean adolescents participated (aged 10–14; 50.7% boys). Cardiorespiratory fitness (CRF), muscular fitness (MF), and speed-agility fitness (SAF) were evaluated, and a global fitness score (GFS) was computed adjusted for age and sex (CRF + MF + SAF z-scores). Body mass index z-score (BMIz), sum-of-4-skinfolds (4SKF), and waist-to-height ratio (WHtR) were used as non-specific, peripheral, and central adiposity indicators, respectively. A global cognitive score was computed based on eight tasks, and the school vulnerability index (SVI) was registered as high, mid or low. A total of 24 mediation analyses were performed according to two models, adjusted for sex and peak high velocity (Model 1), and adding the school vulnerability index (SVI) in Model 2. The significance level was set at p < 0.05. Results: The fitness mediation role was different concerning the fatness indicators related to fat distribution analyzed. Even after controlling for SVI, CRF (22%), and SAF (29%), but not MF, mediated the association between BMIz and cognitive performance. Likewise, CRF, SAF and GFS, but not MF, mediated the association between WHtR and cognitive performance (38.6%, 31.9%, and 54.8%, respectively). No mediations were observed for 4SKF. Conclusion: The negative association between fatness and cognitive performance is mitigated by the level of adolescents’ physical fitness, mainly CRF and SAF. This mediation role seems to be more consistent with a central fat indicator even in the presence of school vulnerability. Strategies promoting physical fitness would reduce the cognitive gap in children and adolescents related to obesity and school vulnerability.